The Effect on Food Intake and Nutrient Digestibility of Ensiling by Mixing Whole Crop Barley at the Boot Stage with Sainfoin in Lambs - Tatli, Pinar; Çerçi, I. Halil; Azman, M. Ali; Gürdo?an, Fuat (My University, 2001)
This study was conducted to determine of effects on food intake and nutrient digestibility of ensiling by mixing different proportions of whole crop barley at the boot stage including low dry matter and high easy dissolve carbohydrate with sainfoin including high dry matter and crude protein in lambs. Five Akkaraman male lambs averaging 42 kg and 12 months old were used. The experiment was carried out according to the 5X5 latin square design in individual boxes. The study groups were determined according to the proportions of whole crop barley and sainfoin which were used as silage materials. Group I (100 K) included 100% sainfoin: Group II (75K+25A) included 75% sainfoin + 25% whole crop barley; Group III (50 K+50 A) included 50% sainfoin + 50% whole crop barley; Group IV (25 K+75 A) included 25% sainfoin + 75% whole crop barley; Group V (100 A) included 100% whole crop barley. The pH of silages were determined to be 4.8, 4.6, 4.6, 4.5 and 4.5 in the groups, respectively. Dry matter levels of silages were determined to be 36.20, 33.72, 31.51, 29.03 and 25.72%, respectively. Dry matter intakes of lambs were determined to be 1282.02, 1176.32, 1061.29, 1055.29 and 906.37 g. respectively (P<0.05). Dry matter, crude protein and cellulose digestibility were determined to be 67.69, 67.10, 66.01. 65.78 and 65.22%; 71.15. 68.59, 67.99, 67.06 and 66.92%; and 68.27, 67.78, 67.14, 66.10 and 65.15%, respectively (P>0.05).
Körpe Arpa Hasili ile Korunga Karmasi Silajinin Koyunlarda Yem Tüketimi ve Ham Besin Maddelerinin Sindirilme Derecesine Etkisi
Keywords: Lamb; Sainfoin; Silage; Whole Crop Barley